2022
DOI: 10.1186/s12933-022-01496-7
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous treatment effects of intensive glycemic control on major adverse cardiovascular events in the ACCORD and VADT trials: a machine-learning analysis

Abstract: Background Evidence to guide type 2 diabetes treatment individualization is limited. We evaluated heterogeneous treatment effects (HTE) of intensive glycemic control in type 2 diabetes patients on major adverse cardiovascular events (MACE) in the Action to Control Cardiovascular Risk in Diabetes Study (ACCORD) and the Veterans Affairs Diabetes Trial (VADT). Methods Causal forests machine learning analysis was performed using pooled individual data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…In addition, the use of hypoglycaemic drugs may have an impact on the level of HGI. 22 We performed sensitivity analyses in a population of diabetics who had received treatment, and similar results were obtained. Therefore, the determination of HGI thresholds is of clinical relevance.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…In addition, the use of hypoglycaemic drugs may have an impact on the level of HGI. 22 We performed sensitivity analyses in a population of diabetics who had received treatment, and similar results were obtained. Therefore, the determination of HGI thresholds is of clinical relevance.…”
Section: Discussionmentioning
confidence: 70%
“…Our study observed sex differences between HGI and mortality, particularly CVD mortality. In addition, the use of hypoglycaemic drugs may have an impact on the level of HGI 22 . We performed sensitivity analyses in a population of diabetics who had received treatment, and similar results were obtained.…”
Section: Discussionmentioning
confidence: 78%
“…Setting a glycaemic goal to a specific subpopulation for optimal health outcomes has been a decade‐long debate with mixed evidence because of the variation of patient populations, achieved HbA1c levels and statistical approaches in the study. Post‐hoc studies 23,24 of the ACCORD trial indicated that among (a) younger participants with lower BMI and haemoglobin glycosylation index, or (b) impaired renal function and lower haemoglobin glycosylation index, intensive glucose control was associated with lower risk of mortality or MACE. A post‐hoc analysis of the ADVANCE trial 25 showed that baseline HbA1c was not an effect modifier for intensive glucose control in preventing MACE.…”
Section: Discussionmentioning
confidence: 99%
“…It has long been recognized that hyperglycemia has adverse effects on the vasculature, and diabetes treatment guideline recommendations for intensive glucose lowering for T2DM patients have therefore been implemented for decades [ 13 ]. Data from recent studies seemingly showed that intensive glycemic control to achieve normal or near-normal HbA1c levels was potentially beneficial to delay the progression of microvascular or macrovascular complications and improve prognosis [ 14 17 ]. However, regarding T2DM patients with HFrEF, we found an unexpected risk with intensive glycemic control, which conveyed a more than 2-fold risk of adverse outcomes compared with modest glycemic control.…”
Section: Discussionmentioning
confidence: 99%